Analysis of modern means of creating a device vibration impact on critical infrastructure information system - Корченко, Олександр Григорович; Терейковський, Ігор Анатолійович; Косюк, Євген Сергійович (Ukrainian Information Security Research Journal, 2016)
The methods and means of infrasound impact on critical computer hardware infrastructure. It has been shown that a significant threat to critical infrastructure computer systems is caused by the destructive effect of infrasound waves. At the same time, most of the methods of devices: a Helmholtz resonator, generation by using a pulsating sphere such as monopolies, radiator-type rotor resonating cylinder, the sub column method of paired ultrasonic transducers, propeller. The study of these devices. Revealed their characteristic features, advantages and disadvantages. Charting infrasound radiation pattern and a graph of the volume of infrasound radiation from spent power. Also, as a result of the above devices, reasonable set of basic parameters, the values of which make it possible to assess their structural - operational properties. Also, for each of the methods of generation have been calculated approximate values of these parameters, you can go to further research in order to create a system of classification tools for creating vibration exposure devices and the method of choice method of generating infrasound signal, depending on the expected conditions of use and creation.